2015
DOI: 10.1016/j.cell.2015.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Contributes to the Seasonality of Multiple Sclerosis Relapses

Abstract: SUMMARY Seasonal changes in disease activity have been observed in multiple sclerosis, an autoimmune disorder that affects the central nervous system. These epidemiological observations suggest that environmental factors influence the disease course. Here we report that melatonin levels, whose production is modulated by seasonal variations in night length, negatively correlate with multiple sclerosis activity in humans. Treatment with melatonin ameliorates disease in an experimental model of multiple sclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
215
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(243 citation statements)
references
References 67 publications
14
215
2
5
Order By: Relevance
“…Melatonin has been shown to have immunomodulatory properties and was recently implicated in the development of MS 36. While melatonin was not studied with the metabolomics platform used in our study, serotonin levels were not associated with MS risk or disease severity.…”
Section: Discussionmentioning
confidence: 76%
“…Melatonin has been shown to have immunomodulatory properties and was recently implicated in the development of MS 36. While melatonin was not studied with the metabolomics platform used in our study, serotonin levels were not associated with MS risk or disease severity.…”
Section: Discussionmentioning
confidence: 76%
“…The summer peak in relapse rates was explained by higher temperatures leading to immunological modulations, in particularly to a change in leukocyte nitric-oxide production (Beenakker et al, 2001;Oqawa et al, 2004). A complementary immunological explanation from a recently conducted study are the summer troughs of melatonin production, which ultimately lead to the induction of pathogenic Th17-cell differentiation, inhibition of protective T-regulatory cells, and deactivation of IL-10 promotors (Farez et al, 2015). Further studies are warranted to clarify these hypotheses as possible reasons for the increase in relapse rates during summer.…”
Section: Discussionmentioning
confidence: 99%
“…The pineal gland dysfunction may be pathogenetic factor of such immune disturbances. Thus, in MS patient's melatonin decreases the formation of pathogenic Th17 T cells, cytokine interleukin (IL)-17 and stimulates formation of protective Tr1 regulatory cells and anti-inflammatory cytokine IL-10 [55]. We have shown that old organism's response at neurodegenerative pathology (multiple sclerosis) to the influence of neurotrophic factors may be changed [56].…”
Section: Multiple Sclerosismentioning
confidence: 99%